2006
DOI: 10.1515/bc.2006.106
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular granzymes: current perspectives

Abstract: Granzyme A (GrA) and granzyme B (GrB) play key roles in the induction of target cell death induced by cytotoxic lymphocytes. Whilst these roles have been extensively studied, it is becoming apparent that both granzymes also possess extracellular activities. Soluble granzymes are found extracellularly in normal plasma and are elevated in a number of diseases, ranging from viral and bacterial infections to autoimmune diseases. Here, we discuss the current knowledge of extracellular granzyme substrates, inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
153
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(159 citation statements)
references
References 98 publications
(73 reference statements)
4
153
0
1
Order By: Relevance
“…Using timelapse microscopy, we confirmed that treatment of MC57s with sublytic Pfp alone or with mGzmA S-A and Pfp did not induce death or changes in cell morphology (Figure 2c). Treatment with (active) mGzmA alone resulted in target cell detachment, most likely due to GzmA-mediated cleavage of cell adhesion proteins; [14][15][16] however, the cells continued to proliferate and remained viable after 24 h ( Figures 2b and c, Supplementary Figure S2I). In contrast, treatment with mGzmA and Pfp produced the characteristic elongated morphology of GzmB À / À NK-induced alternate death ( Figure 2civ, Supplementary Movie S4).…”
Section: Resultsmentioning
confidence: 99%
“…Using timelapse microscopy, we confirmed that treatment of MC57s with sublytic Pfp alone or with mGzmA S-A and Pfp did not induce death or changes in cell morphology (Figure 2c). Treatment with (active) mGzmA alone resulted in target cell detachment, most likely due to GzmA-mediated cleavage of cell adhesion proteins; [14][15][16] however, the cells continued to proliferate and remained viable after 24 h ( Figures 2b and c, Supplementary Figure S2I). In contrast, treatment with mGzmA and Pfp produced the characteristic elongated morphology of GzmB À / À NK-induced alternate death ( Figure 2civ, Supplementary Movie S4).…”
Section: Resultsmentioning
confidence: 99%
“…Purified mitochondria from Jurkat cells were treated with GrB (160 nM) for the indicated time periods. Subsequently, the mitochondria were left untreated (left; lanes [1][2][3][4][5][6] or treated with proteinase K (30 g/ml for 10 min followed by 1 M phenylmethylsulfonyl fluoride to stop the reaction; right, lanes [7][8][9][10][11][12]. The mitochondria were then spun to separate the pellets and their supernatants.…”
Section: F and H)mentioning
confidence: 99%
“…The granzyme family of serine proteases are pivotal mediators of apoptosis utilized by cytotoxic lymphocytes against targets such as virus-infected cells and tumor cells (1)(2)(3)(4)(5)(6). Granzyme B (GrB) 3 exerts its cytotoxic effect after perforin-dependent intracellular delivery, acting in both cytosolic and nuclear compartments.…”
mentioning
confidence: 99%
“…Although SERPINB9 is an efficient inhibitor of gzmB inside the cell, gzmB is also known to be present and active extracellularly, where it is likely to be involved in the degradation of extracellular matrix molecules, [62][63][64][65][66][67] and may have pathophysiological functions in blood coagulation 63 and atheromatous disease (reviewed by Chamberlain and Granville 68 and elsewhere in this volume). Past investigations into potential extracellular inhibitors of gzmB have suggested a2-macroglobulin or SERPINA1 as possible candidates; 69 however, SERPINA1 shows no gzmB inhibitory activity in vitro.…”
Section: Regulation Of Extracellular Gzmbmentioning
confidence: 99%
“…However, gzmA does have a range of extracellular substrates (reviewed by Buzza and Bird 62 ) and it has been proposed that its activity in plasma is controlled by SERPINC1 (antithrombin III). 82 SERPINC1 is best characterised as an inhibitor of factor Xa and thrombin in the clotting cascade (reviewed by Pike et al 12 ), and as such it circulates at very high concentrations.…”
Section: Serpinc1 and Granzyme Amentioning
confidence: 99%